KONTROVERSI PUTUSAN MAHKAMAH KONSTITUSI TENTANG PERKAWINAN DI BAWAH TANGAN (Studi Tentang Hukum Perkawinan Antara Normatif dengan Empiiris untuk Menggali Maqashid-AL-Syari’ah dalam Upaya Mewujudkan fikih Indonesia) - Ahmad Khisni (UNISSULA, 2014)
This research aims to identify and assess the normative legal review of the marriage under the hand, knowing the decision of the Constitutional Court and legal considerations as well as to understand and assess the various opinions pro and con about the Constitutional Court’s decision on marriage under the hand. The research method is an object of research is the decision of the Constitutional Court No. 46 / PUU-VIII / 2010, with the approach of case method approach and data collection techniques such as literature studies and decisions with qualitative analysis. The conclusion of this study is a marriage under the new hand a legal effect, namely a result that has the right to receive legal recognition and protection if they meet the Article 2 paragraph (2) of the Act. No. 1 Year 1974. The Constitutional Court argued Article 43 paragraph (1) of Law No. 1 Year 1974 should read: “children born out of wedlock only have a civil relationship with her mother and her mother’s family, as well as his father’s men who can be proved by science and / or other evidence according to the law have blood relations, including relations with civil his father’s family. Pros and cons of the decision of the Constitutional Court concerns only child of a child of the Sirri marriage not the result of adultery. Regarding the child of adultery did not have nasab relationship, guardian of marriage, inheritance and living with a man who caused his birth but has a legal relationship with his mother and his mother’s family